Cytogenetic and Statistical Study on Klinefilter´S Syndrome in Baghdad - Jafer, Suad Gazi; Saleh, Zeina Tarek; Mutlake, Abtesam Hadi (Al-Nahrain Journal of Science, 2018)
This study was carried out to determine the percentage and chromosomal karyotyping in patients with klinfelter`s syndrome in Baghdad. One hundred cases collected from Infertility and I.F.V Center in Baghdad & Yarmok Hospital during the period (2006-2009) to determine the frequency of Klinefilter ´s syndrome. In I.V.F Center hundred infertile male studied Klinefilter form 1.5% percentage of infertile men and statistical study in Yarmok hospital illustrated Klinefilter form 5.2% of patients admitted in situation for mental deficiencies .The statistical study conclusion that Klinefilter`s syndrome varies according to the cases kind Chromosomal analysis &seminal examine for cases with Klinfelter`s syndrome according to the clinical feature and symptoms which related to Klinefilter, small testes (<10mm.), breast enlargement, reduced facial and body hair were studied karyotype. The Chromosomal study illustrated first karyotype of three cases abnormal number for sex chromosome(tow X chromosome) 47, XXY and one case with mosaic karyotape 46, XY / 47, XXY . General seminal examination illustrated aizoospermia for all cases .The Cytogenetic study conclusion that percentages of cases with only abnormal metaphase 75% while the case with mosaic metaphase 25%.